Treatment of radiation-induced vulvar pain via pudendal nerve block under fluoroscopic guidance - Ji Hyeong Yu (Urology Case Reports, 2020)
Vulvar pain is a common complaint in women during reproductive and post-reproductive years. A 70-year-old woman experienced severe intractable vulvar pain after bladder cancer surgery and adjuvant radiation therapy. We performed five fluoroscopy-guided pudendal nerve blocks. Her numeric rating scale decreased from 10 to 3, and after 5 months, her pain was controlled only with oral medication. Pudendal nerve block might stop ongoing sensitization which lead acute nociceptive vulvar pain into chronic neuropathic vulvodynia by attenuating nociceptive stimulation and inflammation.